Learning process in children and adolescents potentialized through social networks (Docentes 2.0 Journal, 2019)
The research aimed to analyze the use of social networks and their negative effect on the learning process in children of the educational institutions of the Riohacha municipality.  It was descriptive in nature with a non-experimental, transectional and field design; a three-aspect content instrument was used for parents and two for teachers of the institution. The sample consisted of 50 teachers and 100 parents from 10 institutions of the municipality. The results indicate that the social networks most used by children and adolescents are WhatsApp, Telegram, Instagram and Snapchat, as well as the effects on learning behaviors that were evidenced: mood modification, salience, abstinence and lack of attention. It is recommended as parents to have mastery of content and forms of social networks and as an institution to establish schedules for the use of social networks and incorporate extra-academic activities to consolidate comprehensive training, with the effect of co-responsibility.
Keywords: Social networks; learning in children and adolescents; behavioral effects